Persepsi Mahasiswa Terhadap Peran Pasien Simulasi dalam Ujian OSCE di Fakultas Kedokteran Universitas Islam Indonesia - Nurul Fajar Ramadhany; Umatul Khoiriyah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2011)
One way to improve the quality of psychomotor skills to medical students is implementation of medical skills. Learning activities of medical skills in FK UII are communication skill, physical examination and procedural skill. Various activities of medical skill are largely carried out by using mannequins and imulated patients (SPs). Objective Structural Clinical Examination (OSCE) is used to assess the student’s performance in medical skills. The aim of this  esearch is to know the student’s perceptions about the role of SPs in the OSCE in FK UII and to find out the criteria of SPs desired by the students in assisting the activities of medical skills in FK UII.This research was conducted in FK UII through in-depth interviews. The respondents were 12 students from academic year of 2007, 2008, and 2009, for each year was taken 4 students. Based on criteria of active students and always take the OSCE exam in FK UII, then taken 2 students with the highest GPA and 2 students with the lowest GPA from each year. The information was analyzed using a constant comparative method by reducing the data using a coding system, categorizing data, synthesizing, and making a working hypotheses.The results show that the roles of SPs accordingto student’s perceptions are to help learning medical skills; to assist OSCE exam; and to train students before encounter with the real patients. Simulated patients in FK UII are often asked many questions, less cooperative, but more friendly. Most of SPs in FK UII are less appreciate in their acting. Simulated patients in FK UII are usually less understand about the disease, they act only based on the scenarios and the information presented by SPs is also less clear. In addition, SPs never give feedback to students. Students expect that SPs can act and appreciate their role very well, and can be more cooperative. So, simulated patients (SPs) in FK UII, especially that were played by non educative staff, were not conducted in student’s expectation. Keyword : Skills Lab-Simulated Patients-OSCE